Knee hemarthrosis after arthroscopic surgery in an athlete with low factor XIII activity - Tsujii Akira; Tanaka Yoshinari; Yonetani Yasukazu; Shiozaki Yoshiki; Tomiyama Yoshiaki; Horibe Shuji (BMC, 2012)
Abstract We report a thirteen-year-old tennis player with knee hemarthrosis caused by low factor XIII activity. She visited our hospital because of medial peripatellar pain for two years. Although there was no abnormal sign in X-ray or MRI, diagnostic arthroscopy was performed. It revealed some cartilage debris, medial plica and complete septum of suprapatellar plica. Removing the debris by washing out and resecting the medial plica, she could return to play tennis without perioperative symptom. Two months after the first operation, her knee got swelling without any apparent cause. Since 20 ml blood was aspirated twice and MRI revealed suprapatellar mass, we performed arthroscopy again. Suprapatellar mass was old blood clot covered with complete suprapatellar plica. Resection of suprapatellar plica and washing out blood clot were performed, and severe postoperative hemarthrosis was progressively occurred. As factor XIII level was 54% preoperatively, we diagnosed that this condition was caused by low activity level of the factor and administered factor XIII concentrates. The level got improved to 129% and then hemarthrosis gradually relieved. She had no signs of recurrence. We should keep in mind of low factor XIII activity case in case of unexplained postoperative hemarthrosis after arthroscopy because consumption of the factor might promote this condition.